2019
DOI: 10.17015/ejbe.2019.024.03
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Oil Prices and Exchange Rate Shocks on Inflation: Evidence from India

Abstract: The purpose of this study is to examine the long-run and short-run impact of crude oil price and exchange rate shocks on domestic inflation in India within the framework of the Autoregressive Distributed Lag (ARDL) model. The results show that the exchange rate and oil price shocks significantly influence domestic inflation during the study period (April 1994 to February 2018. Further, the breakpoint unit root test revealed the severe impact of the 2008 financial crisis on inflation in India. The findings show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This phenomenon can be explained by the theory of "Effective Wealth", which suggests that an increase in oil prices can increase the wealth of oil-producing countries, stimulating investment and financial transactions (Hamilton, 1983). In addition, the literature highlights the influence of oil revenues on the financial system and investment, supporting the idea that changes in the price of oil can affect financial activity (Kilian and Park, 2009;Tala and Hlongwane, 2023;Sharma and Dahiya, 2023;Neifar and Kammoun, 2022).…”
Section: Resultsmentioning
confidence: 88%
“…This phenomenon can be explained by the theory of "Effective Wealth", which suggests that an increase in oil prices can increase the wealth of oil-producing countries, stimulating investment and financial transactions (Hamilton, 1983). In addition, the literature highlights the influence of oil revenues on the financial system and investment, supporting the idea that changes in the price of oil can affect financial activity (Kilian and Park, 2009;Tala and Hlongwane, 2023;Sharma and Dahiya, 2023;Neifar and Kammoun, 2022).…”
Section: Resultsmentioning
confidence: 88%
“…This resonates with the argument that as a result of the oil dependent nature of GCC states, their economies become very sensitive to oil price fluctuations (Maghyereh et al, 2020;Jawadi and Ftiti, 2019; Gray 2011). To clearly highlight similar studies on the GCC region, other studies have also studied the relationship of oil price fluctuations on GDP growth and on income sustainability as well as other impacts of oil price on microeconomic variables of a country (Murshed et al, 2020;Chang et al, 2020;Tala and Hlongwane, 2023;Balcilar et al, 2019;Badeeb and Lean, 2018;Basher et al, 2018;Neifar and Kammoun, 2022;Sharma and Dahiya, 2023;Salisu and Oloko, 2015;Musa 2010). In another related study Nasir et al, (2019) revealed the impact of oil price on macroeconomic variables in GCC member countries between 1980-2016. the studies mentioned above observed a heterogenous response of GCC member countries on oil price shocks.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The primary goal of the study is to estimate how variables affect oil prices using a quarterly data set for all variables from 2011 to 2021. Sharma & et al (2019) [5] it was argued that the passthrough effect of the oil price and exchange rate on economic activity, particularly in developing economies, presents policymakers with a nightmare at all times. In energy-dependent economies, exchange rate and oil price fluctuations have a significant impact on economic expansion and inflation, ultimately destabilizing the monetary and financial system of the economy."…”
Section: Literature Reviewmentioning
confidence: 99%